Value Innovation in the Malaysian Retail Industry - Fong, Hui Sain (2013)
The retail industry is a key driver of domestic consumption in Malaysia and an important contributor to the nation’s income. Today’s challenging economic and competitive environment entails that retailers need to invest in innovation that will bring growth and added value. This study combines three key concepts: the resource-based view, institutional theory and McNair’s Wheel of Retailing, to explore how innovation enhances the value-creation process in the industry, what institutional forces influence the practice of innovation itself, whether there are any emerging patterns within the process of retailing innovation over the years, and whether these were incremental innovations or real game-changing value innovations that resulted in higher performance, and thus superior competitive advantage. The research reveals that though the awareness of the importance of innovation was high, retailing innovation in practice is thought to be lacking in Malaysia. Certain perceived recurring cycles of innovation in the Malaysian retail industry are identified in the findings, where innovation is triggered by various catalysts at different stages of the retailing organisation’s development. The initial market entry stage is where innovation is probably at its’ highest. Subsequently, institutionalization often sets in during the trading-up phase, leading to only incremental innovation, and thus temporary competitive advantage. The retailer has to continuously innovate, and when it reaches a vulnerable phase, radical innovation of a disruptive nature is required for renewed long-term growth and profits. The study shows that continuous value innovation is necessary for the survival of a retailer at every stage of its lifecycle. Retailers must be conscious of the influence of institutionalization and what constitutes real value innovation to sustain their competitive advantage.